Near-infrared low-potential electrochemiluminescence double-ligand stable gold nano-cluster as well as preparation method and application thereof

By developing biligand-stable gold nanoclusters and using thiomalic acid and citrate coated gold nanoclusters, the problems of high potential and co-reactant toxicity of existing electrochemiluminescence systems are solved, and low-potential near-infrared electrochemiluminescence and high-efficiency aqueous system applications are realized.

CN119899655AActive Publication Date: 2025-04-29QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411840675.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-12
Filing Date
2024-12-13
Publication Date
2025-04-29
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing electrochemiluminescence systems have problems such as excessive potential, oxidation damage to biochemical samples, electrochemical interference and poor electrode tolerance. Traditional co-reactants such as hydrazine hydrate are toxic and the electrochemiluminescence efficiency of the carbohydrazide system is low.

Method used

A stable gold nanocluster of near-infrared low-potential electrochemiluminescent biligand was developed, and the gold nanoclusters were coated with thiomalic acid and citrate as biligands were prepared to produce low-potential near-infrared electrochemiluminescence in an aqueous phase system.

Benefits of technology

It is realized that low-potential near-infrared electrochemiluminescence with a maximum emission wavelength of more than 800nm ​​and a minimum radiation potential of less than 0.60V in the aqueous phase system is generated, which breaks away from the dependence of traditional electrochemiluminescent substances on hydrazine hydrate or carbohydrazide, and uses a non-toxic tert-butylamine-borane co-reactant to produce low-potential electrochemiluminescence radiation of 0.57V.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005187898530000011
    Figure HDA0005187898530000011
  • Figure HDA0005187898530000012
    Figure HDA0005187898530000012
  • Figure HDA0005187898530000021
    Figure HDA0005187898530000021
Patent Text Reader

Abstract

The invention relates to a near-infrared low-potential electrochemiluminescence double-ligand stable gold nanocluster and a preparation method and application thereof.The method is characterized in that chloroauric acid serves as a gold source, thiomalic acid and sodium citrate serve as a reducing agent and a stabilizing agent, and the gold nanocluster is synthesized through a two-step method and comprises the steps that firstly, a water-soluble gold nanocluster is prepared on the basis of a thiomalic acid online reduction Au < 3 + > principle method; then incubating with sodium citrate, and synthesizing the thiomalic acid and sodium citrate co-coated gold nanocluster on the basis of a ligand exchange principle. The required raw materials are easy to obtain and have good water solubility, a synthesis device is simple, conditions are mild, and operation is safe. The obtained double-ligand-coated gold nanocluster is good in stability, generates low-potential near-infrared electrochemical luminescence located in a long-wave region in a water phase system, gets rid of the limitation that most electrochemical luminescence substances are matched with hydrazine hydrate or carbohydrazide at present, and adopts a non-toxic tert-butylamine-borane co-reaction agent, so that the electrochemical luminescence efficiency is improved. And low-potential electrochemiluminescence radiation of 0.57 V in a near-infrared region is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanocluster and a preparation method and application thereof, belonging to the field of analytical technology methods. Background Art

[0002] Electrochemiluminescence is a unique light radiation phenomenon produced when an electrically excited luminescent substance changes from an excited state to a ground state. The characteristics of electrochemiluminescence are determined by the electrochemiluminescent substance and the co-reactant. The development of new electrochemiluminescence systems, that is, matching electrochemiluminescent reagents and co-reactants, has always occupied an important position in the field of electrochemiluminescence. For example, based on Ru(bpy)3 2+ Electrochemiluminescence kits of tri-n-propylamine (TPrA) system and corresponding supporting instruments and equipment have occupied the field of in vitro diagnosis at home and abroad for many years, so it is urgent to develop new electrochemiluminescent reagents and matching electrochemiluminescent systems to achieve performance improvement. Bard's research group first reported the electrochemiluminescence of Si nanoparticles in 2002 (Science 2002, 296, 1293), and then the electrochemiluminescence of nanomaterials represented by II-VI quantum dots has made a series of progress (Chem. Rev. 2014, 114, 11027). I-VI quantum dots usually contain toxic elements and have potential environmental toxicity and biological toxicity exposure risks. Therefore, the electrochemiluminescence of gold, silver, and copper metal nanoparticles with good biocompatibility is gaining widespread attention.

[0003] Classic Ru(bpy)3 2+ The electrochemiluminescence potential of the / TPrA system is too high (1.2V vs Ag / AgCl), which can easily cause oxidative damage to biochemical samples, which is not conducive to reducing electrochemical interference and improving electrode tolerance. Liu et al. confirmed that in the presence of dissolved oxygen, CdTe quantum dots on paraffin-impregnated graphite electrodes can produce electrochemiluminescence at a low potential of ~0.89V (vs Ag / AgCl) (Analyst 2008, 133(9), 1161). Liang et al. found that CdTe quantum dots with dual ligands as stabilizers have two obvious redox ECL processes, with the lowest peak potential being ~0.63V (vs. Ag / AgCl) (Anal. Chem. 2012, 84(24), 10645). Some strongly reducing chemicals such as hydrazine hydrate and carbohydrazide have been confirmed to be a co-reactant that can produce low-potential electrochemiluminescence (Anal. Chem. 2020, 92(8), 6144; 2019, 91(15), 10221). However, hydrazine hydrate is highly toxic, and the electrochemiluminescence efficiency of the carbohydrazide system is lower than that of the hydrazine hydrate system. However, most of the current electrochemiluminescent materials are mostly matched with hydrazine hydrate or carbohydrazide.

[0004] Therefore, the development of new electrochemiluminescent reagents with low hole injection potentials and safe, non-toxic co-reactants with lower oxidation potentials is of great significance for achieving low-potential electrochemiluminescence radiation. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanocluster and a preparation method and application thereof.

[0006] The dual-ligand stabilized water-soluble gold nanoclusters provided by the present invention can generate low-potential near-infrared electrochemical luminescence in the long-wave region in an aqueous phase system under the condition of a co-reactant, with a maximum emission wavelength exceeding 800nm ​​and a minimum radiation potential less than 0.60V.

[0007] The present invention is achieved through the following technical solutions:

[0008] A near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanocluster is a gold nanocluster co-coated with citrate and thiomalic acid dual ligands and has a spherical shape with a diameter of 1-5 nm.

[0009] Preferably according to the present invention, the aqueous solution of the gold nanocluster material is brown-yellow, has a strong absorption peak at 564nm in the UV-visible spectrum, has a maximum fluorescence emission wavelength at 815nm, no obvious fluorescence is observed under UV light, and its maximum electrochemical luminescence wavelength is 835nm.

[0010] The second object of the present invention is to provide a method for preparing the above-mentioned near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanoclusters.

[0011] The preparation method of the near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanoclusters uses chloroauric acid as a gold source, first uses thiomalic acid as a reducing agent and stabilizer, and then reduces Au by thiomalic acid. 3+ , single-ligand-stabilized water-soluble gold nanoclusters were prepared, and then the single-ligand-stabilized water-soluble gold nanoclusters were mixed, stirred and incubated with citrate to obtain thiomalic acid and sodium citrate dual-ligand-stabilized gold nanoclusters.

[0012] According to the present invention, preferably, the method for preparing the near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanoclusters comprises the following steps:

[0013] (1) Ultrasonic mixing of chloroauric acid (H4AuCl4) solution and thiomalic acid (MSA) ligand;

[0014] (2) heating the solution obtained in step (1) to react, thereby obtaining single-ligand-stabilized water-soluble gold nanoclusters, and the solution changes from colorless to brown-yellow;

[0015] (3) adding citrate (Cit) to the solution prepared in step (2), mixing by ultrasonication, and incubating at room temperature;

[0016] (4) After the reaction is completed, the large particles at the bottom are removed by centrifugation, and the solution is purified by isopropanol. The resulting precipitate is the dual-ligand stabilized gold nanoclusters.

[0017] According to the present invention, preferably, in step (1), the molar ratio of gold in chloroauric acid to thiomalic acid is 1:(1-5),

[0018] Most preferably, the molar ratio of gold to thiomalic acid in chloroauric acid is 1:3.

[0019] According to the present invention, preferably, in step (1), the concentration of the H4AuCl4 solution is 80-100 mM.

[0020] According to the present invention, preferably, in step (2), the heating temperature is 90-100° C. and the heating time is 130-150 h.

[0021] According to the present invention, preferably, in step (3), the molar ratio of citrate to gold in chloroauric acid is 1:350-500.

[0022] According to the present invention, preferably, in step (3), the incubation time at room temperature is 0.5-3h.

[0023] According to the present invention, preferably, in step (4), the isopropanol is purified by adding isopropanol to the solution and centrifuging at 13,000-14,000 rpm.

[0024] In a preferred embodiment of the present invention, a method for preparing infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanoclusters comprises the following steps:

[0025] (1) 610-650 μL of 96 mM H4AuCl4 solution and 10-30 mL of 9.6 mM thiomalic acid solution were ultrasonically mixed, and the mixture was heated under reflux at 90-100° C. for 130-150 h to obtain thiomalic acid-coated gold nanoclusters;

[0026] (2) mixing a 0.1-0.3 mM citrate solution with the solution obtained in step (1), ultrasonically mixing, and incubating at room temperature for 1 hour to obtain gold nanoclusters coated with citrate and thiomalic acid as dual ligands;

[0027] (3) The solution obtained in step (2) is purified by centrifugation with isopropanol, and the resulting precipitate is the dual-ligand stabilized gold nanoclusters.

[0028] The application of the above-mentioned dual-ligand stabilized water-soluble gold nanoclusters produces low-potential electrochemiluminescence radiation in the near-infrared region under the conditions of tert-butylamine-borane co-reactant.

[0029] The technical features and advantages of the present invention are as follows:

[0030] 1. The present invention obtains gold nanoclusters stabilized by dual ligands of thiomalic acid and sodium citrate through a two-step method. The prepared gold-silver nanoclusters have the advantages of being free of toxic elements, having good bioaffinity and being stable in storage.

[0031] 2. The dual-ligand stabilized gold nanoclusters prepared by the present invention can generate low-potential electrochemiluminescence radiation in the near-infrared region in an aqueous system, with a maximum emission wavelength of 835nm, exceeding 800nm, and a minimum radiation potential of less than 0.60V. The preparation method has simple steps, mild conditions, and safe operation.

[0032] 3. The present invention successfully synthesized a new type of electrochemiluminescent reagent with low hole injection potential, which can produce low-potential near-infrared electrochemiluminescence in the long-wave region in an aqueous phase system under the condition of tert-butylamine-borane co-reactant, breaking away from the limitation that most current electrochemiluminescent materials must match hydrazine hydrate or carbohydrazide, and using non-toxic tert-butylamine-borane co-reactant, it produces low-potential electrochemiluminescence radiation of 0.57V in the near-infrared region. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the X-ray energy spectrum analysis spectrum of the dual-ligand stabilized gold nanoclusters prepared in Example 1.

[0034] Figure 2 This is a high-magnification transmission electron microscope photograph of the dual-ligand stabilized gold nanoclusters prepared in Example 1.

[0035] Figure 3 This is the fluorescence spectrum of the dual-ligand stabilized gold nanoclusters prepared in Example 1.

[0036] Figure 4 This is the ultraviolet spectrum of the dual-ligand stabilized gold nanoclusters prepared in Example 1.

[0037] Figure 5 This is the electrochemiluminescence spectrum of Example 2, the potential window is 0-1.6V, the scanning speed is 50mV / s; the abscissa is the wavelength, and the ordinate is the electrochemiluminescence intensity.

[0038] Figure 6 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Example 2; the potential window is 0-1.6V, the scan rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity.

[0039] Figure 7 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Comparative Example 1; the potential window is 0-1.6V, the scanning rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity.

[0040] Figure 8 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Comparative Example 2; the potential window is 0-1.6V, the scan rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity.

[0041] Fig. 9 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Comparative Example 3; the potential window is 0-1.6V, the scan rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity.

[0042] Fig.10 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Comparative Example 4; the potential window is 0-1.6V, the scanning rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity.

[0043] Fig.11 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Comparative Example 5; the potential window is 0-1.6V, the scan rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity.

[0044] Fig.12 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Comparative Example 6; the potential window is 0-1.6V, the scan rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity.

[0045] Fig.13 This is the electrochemical luminescence intensity-(potential) time curve driven by cyclic voltammetry of Comparative Example 7; the potential window is 0-1.6V, the scan rate is 50 mV / s; the abscissa is the potential, and the ordinate is the electrochemical luminescence intensity. DETAILED DESCRIPTION

[0046] The present invention is further illustrated by the following examples, but is not limited thereto.

[0047] The fluorescence spectra of the gold and silver nanoclusters described in the examples were collected by a F-4700 fluorescence spectrophotometer.

[0048] The UV-visible absorption spectra were acquired by an Agilent Cary 60 UV-visible spectrophotometer.

[0049] The electrochemiluminescence spectrum was acquired by the GCFG-A electrochemiluminescence spectrum acquisition system developed by Shandong Guochen Biotechnology Co., Ltd. The potential window used was 0-1.6V, and the scanning speed was 50mV / s.

[0050] Electrochemiluminescence test: 10 μL of 2 mg / mL dual-ligand stabilized gold nanocluster solution was drop-coated on the surface of the glassy carbon electrode and dried to prepare a gold nanocluster modified electrode. The gold nanocluster modified electrode was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, and the Pt wire was used as the counter electrode. The test solution was a 0.1 mol / L phosphate buffer solution (pH 7.4) containing different co-reactants at a concentration of 10 mmol / L; the collected electrochemiluminescence spectrum was the integrated spectrum of all ECL radiation.

[0051] The vessels used in the examples were soaked in freshly prepared aqua regia for 24 hours, rinsed thoroughly with ultrapure water and ethanol, and then dried in air.

[0052] Example 1

[0053] Preparation of infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanoclusters:

[0054] (1) 625 μL of 96 mM H4AuCl4 solution and 20 mL of 9.6 mM thiomalic acid solution were ultrasonically mixed and added to a three-necked flask, and then heated under reflux at 95°C for 144 h to obtain thiomalic acid-coated gold nanoclusters. The solution changed from colorless to brown-yellow.

[0055] (2) Weigh 0.15 mM sodium citrate solution and mix it with the thiomalic acid-coated gold nanoclusters prepared in step (1), mix them by ultrasonication, the molar ratio of sodium citrate to H4AuCl4 is 1:400, and incubate at room temperature for 1 h;

[0056] (3) adding isopropanol to the solution obtained in step (2), collecting the precipitate by centrifugation at 13,000 rpm, and obtaining dual-ligand stabilized gold nanoclusters.

[0057] The X-ray energy spectrum analysis spectrum of the dual-ligand stabilized gold nanoclusters obtained by testing is shown in Figure 1 .

[0058] Experimental Example 1

[0059] 1. The precipitate collected in step (3) of Example 1 was dried into powder, and a 1 mg / mL solution prepared by mixing the powder was dropped onto a copper mesh to characterize the morphology of the gold nanoclusters. The high-power transmission electron microscopy of the gold nanoclusters showed Figure 2 .from Figure 2 It can be seen that the dual-ligand stabilized gold nanoclusters are spherical particles with a diameter of 3 nm.

[0060] 2. The fluorescence spectrum of the dual-ligand stabilized gold nanoclusters obtained in step (3) of Example 1 was tested. Figure 3 ,from Figure 3 It can be seen that the maximum fluorescence emission wavelength of the prepared dual-ligand gold nanoclusters is at 815 nm, which is in the near-infrared region.

[0061] 3. The UV spectrum of the dual-ligand stabilized gold nanoclusters obtained in step (3) of Example 1 was tested. Figure 4 ,from Figure 4 It can be seen that the prepared dual-ligand gold nanoclusters have an obvious surface plasmon resonance peak at 564nm.

[0062] Example 2

[0063] Application of the dual-ligand stabilized water-soluble gold nanoclusters prepared in Example 1:

[0064] The dual-ligand stabilized gold nanoclusters prepared in step (3) of Example 1 were prepared into a 2 mg / mL dual-ligand stabilized gold nanocluster solution;

[0065] 10 μL of a dual-ligand stabilized gold nanocluster solution was dropped onto the surface of a glassy carbon electrode and dried at room temperature to obtain a gold nanocluster-modified electrode; a three-electrode system was formed using the gold nanocluster-modified electrode as a working electrode, an Ag / AgCl electrode as a reference electrode, and a Pt wire as a counter electrode in a 0.1 mol / L phosphate buffer solution (pH 7.4) containing a 10 mmol / L tert-butylamine-borane co-reactant; the system was driven to emit electrochemiluminescence radiation using a three-electrode system and a cyclic voltammetry scanning method, and the electrochemiluminescence spectrum was collected as the integrated spectrum of all ECL radiation.

[0066] The electrochemiluminescence spectrum obtained by cyclic voltammetry is shown in the figure Figure 5 As shown, from Figure 5 It can be seen that the maximum radiation position of the electrochemiluminescence spectrum of the dual-ligand stabilized gold nanoclusters prepared in Example 1 is located at 835 nm, which is in the near-infrared region.

[0067] The electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is shown in Figure 6 ,from Figure 6 It can be seen that with tert-butylamine-borane as the co-reactant, the maximum electrochemiluminescence radiation potential of the gold nanoclusters of the present invention is at 0.57 V, which is much lower than the traditional bis-ruthenium pyridine / tripropylamine system (1.2 V).

[0068] Comparative Example 1

[0069] The same application as described in Example 2, except that tert-butylamine-borane is replaced by tripropylamine, and the electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is as follows: Figure 7 ,from Figure 7 It can be seen that with tripropylamine as the co-reactant, the dual-ligand stabilized gold nanoclusters emit weak electrochemiluminescence at a low radiation potential of 0.57V, and the maximum electrochemiluminescence radiation potential is much higher than that with tert-butylamine-borane as the co-reactant.

[0070] Comparative Example 2

[0071] The same application as described in Example 2, except that tert-butylamine-borane is replaced by triethylamine, and the electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is as follows: Figure 8 ,from Figure 8 It can be seen that with triethylamine as the co-reactant, the dual-ligand stabilized gold nanoclusters emit weak electrochemiluminescence at a low radiation potential of 0.57V, and the maximum electrochemiluminescence radiation potential is much higher than that with tert-butylamine-borane as the co-reactant.

[0072] Comparative Example 3

[0073] The same application as described in Example 2, except that tert-butylamine-borane is replaced by 2-(dibutylamino)ethanol, and the electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is as follows: Fig. 9 ,from Fig. 9 It can be seen that with 2-(dibutylamino)ethanol as the co-reactant, the dual-ligand stabilized gold nanoclusters emit weak electrochemiluminescence at a low radiation potential of 0.57V, and the maximum electrochemiluminescence radiation potential is much higher than that with tert-butylamine-borane as the co-reactant.

[0074] Comparative Example 4

[0075] The same application as described in Example 2, except that tert-butylamine-borane is replaced by triethanolamine, and the electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is as follows: Fig.10 ,from Fig.10 It can be seen that with triethanolamine as the co-reactant, the dual-ligand stabilized gold nanoclusters emit weak electrochemiluminescence at a low radiation potential of 0.57V, and the maximum electrochemiluminescence radiation potential is much higher than that with tert-butylamine-borane as the co-reactant.

[0076] Example 5

[0077] The same as the application described in Example 2, except that the co-reactant is removed and the electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is as follows: Fig.11 ,from Fig.11 It can be seen that in the absence of a co-reactant, the dual-ligand stabilized gold nanoclusters emit weak electrochemiluminescence at a low radiation potential of 0.57 V, and the maximum electrochemiluminescence radiation potential is much higher than that when tert-butylamine-borane is a co-reactant.

[0078] Comparative Example 6

[0079] Preparation of Thiomalic Acid-Coated Gold Nanoclusters:

[0080] 625 μL of 96 mM H4AuCl4 solution and 20 mL of 9.6 mM thiomalic acid solution were ultrasonically mixed and added to a three-necked flask, and then heated under reflux at 95°C for 144 h. After the reaction was completed, isopropanol was added and the precipitate was collected by centrifugation at 13,000 rpm to obtain thiomalic acid-coated gold nanoclusters.

[0081] The thiomalic acid-coated gold nanoclusters are prepared into a 2 mg / mL thiomalic acid-coated gold nanocluster solution;

[0082] 10 μL of thiomalic acid-coated gold nanocluster solution was dropped onto the surface of a glassy carbon electrode and dried at room temperature to obtain a gold nanocluster-modified electrode; a three-electrode system was formed with the gold nanocluster-modified electrode as a working electrode, an Ag / AgCl electrode as a reference electrode, and a Pt wire as a counter electrode in a 0.1 mol / L phosphate buffer solution (pH 7.4) containing a 10 mmol / L tert-butylamine-borane co-reactant;

[0083] The electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is shown in Fig.12 ,from Fig.12 It can be seen that although the thiomalic acid-stabilized gold nanoclusters can also radiate low-potential electrochemiluminescence at 0.57 V, their electrochemiluminescence radiation intensity is much lower than that of the dual-ligand stabilized gold nanoclusters ( Figure 6 ).

[0084] Comparative Example 7

[0085] Preparation of sodium citrate-coated gold nanoclusters:

[0086] 625 μL of 96 mM H4AuCl4 solution and 20 mL of 0.15 mM sodium citrate solution were ultrasonically mixed and added to a three-necked flask, and then heated under reflux at 95°C for 144 h. After the reaction was completed, isopropanol was added and the precipitate was collected by centrifugation at 13,000 rpm to obtain sodium citrate-coated gold nanoclusters.

[0087] The sodium citrate-coated gold nanoclusters were prepared into a 2 mg / mL sodium citrate-coated gold nanocluster solution;

[0088] 10 μL of sodium citrate-coated gold nanocluster solution was dropped onto the surface of a glassy carbon electrode and dried at room temperature to obtain a gold nanocluster-modified electrode; a three-electrode system was formed with the gold nanocluster-modified electrode as a working electrode, an Ag / AgCl electrode as a reference electrode, and a Pt wire as a counter electrode in a 0.1 mol / L phosphate buffer solution (pH 7.4) containing a 10 mmol / L tert-butylamine-borane co-reactant;

[0089] The electrochemical luminescence intensity-(potential) time curve obtained by cyclic voltammetry is shown in Fig.13 ,from Fig.13 It can be seen that single-ligand stabilized gold nanoclusters (sodium citrate stabilized gold nanoclusters) cannot produce low-potential electrochemiluminescence radiation.

Claims

1. A near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanocluster, wherein the gold nanocluster is a gold nanocluster co-coated with citrate and thiomalic acid dual ligands and has a spherical shape with a diameter of 1-5 nm.

2. The gold nanocluster according to claim 1, characterized in that The aqueous solution of gold nanocluster material is brown-yellow, with a strong absorption peak at 564nm in the UV-visible spectrum; the maximum fluorescence emission wavelength is 815nm, and no obvious fluorescence can be seen under UV light. The maximum wavelength of its electrochemical luminescence is 835nm.

3. The method for preparing the near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanoclusters according to claim 1 or 2, wherein chloroauric acid is used as a gold source, thiomalic acid is used as a reducing agent and a stabilizer, and Au is reduced by thiomalic acid. 3+ , single-ligand-stabilized water-soluble gold nanoclusters were prepared, and then the single-ligand-stabilized water-soluble gold nanoclusters were mixed, stirred and incubated with citrate to obtain thiomalic acid and sodium citrate dual-ligand-stabilized gold nanoclusters.

4. The method for preparing the near-infrared low-potential electrochemiluminescent dual-ligand stabilized gold nanoclusters according to claim 1 or 2, comprising the following steps: (1) Ultrasonic mixing of chloroauric acid (H4AuCl4) solution and thiomalic acid (MSA) ligand; (2) heating the solution obtained in step (1) to react, thereby obtaining single-ligand-stabilized water-soluble gold nanoclusters, and the solution changes from colorless to brown-yellow; (3) adding citrate (Cit) to the solution prepared in step (2), mixing by ultrasonication, and incubating at room temperature; (4) After the reaction is completed, the large particles at the bottom are removed by centrifugation, and the solution is purified by isopropanol. The resulting precipitate is the dual-ligand stabilized gold nanoclusters.

5. The method according to claim 4, characterized in that In step (1), the molar ratio of gold in chloroauric acid to thiomalic acid is 1:(1-5).

6. The method according to claim 4, characterized in that In step (1), the concentration of the H4AuCl4 solution is 80-100 mM.

7. The method according to claim 4, characterized in that In step (2), the heating temperature is 90-100° C. and the heating time is 130-150 h.

8. The method according to claim 4, characterized in that In step (3), the molar ratio of citrate to gold in chloroauric acid is 1:350-500.

9. The method according to claim 4, characterized in that In step (3), the incubation time at room temperature is 0.5-3h. In step (4), isopropanol purification is performed by adding isopropanol to the solution and centrifuging at 13000-14000 rpm.

10. Use of the dual-ligand stabilized water-soluble gold nanoclusters according to claim 1 to generate low-potential electrochemiluminescence radiation in the near-infrared region under the conditions of tert-butylamine-borane co-reactant.

Citation Information

Patent Citations

  • Double-ligand gold nanoparticle aqueous solution and preparation method and application thereof

    CN109986090A

  • Precious metal nano sol as well as preparation method and application thereof

    CN112191859A

  • Electrode, preparation of biosensor containing electrode and application of biosensor in detection of methyltransferase

    CN112730554A

  • Functionalized gold nanoparticles and methods thereof

    US20170131286A1

  • Synthesis of water-soluble thiolate-protected gold nanoparticles of uniform size and conjugates thereof

    US20170304902A1